Consumer Decision Analysis in Purchasing Disposable Diapers Using the Theory of Planned Behavior (TPB) Approach - Aulia Patricia Dellaross Tentua; Hediani Wijono; Desrina Yusi Irawati (Heuristic, 2025)
This study aims to examine the variables that impact the purchasing of disposable diapers by using an enlarged Theory of Planned Behavior (TPB) framework. Two hundred thirty-two people in Surabaya who were familiar with the use of disposable diapers for either infants or the elderly were surveyed online. A quantitative explanatory approach was used to examine this data. Knowledge, Morality, Tradition, and Perceived Risk are new components of the extended TPB model that take into consideration the specific social and cultural context of Indonesia. For this data analysis, we turned to LISREL, which stands for Structural Equation Modeling. The results show that environmental consciousness, understanding, and ethics significantly affect intent, behavior, and result. Some elements that affect the intention to buy include subjective norms and perceived behavioral control; on the other hand, perceived risk and tradition have an adverse effect on these factors. Consistent with the TPB paradigm when applied to one-time use products, these findings highlight the role of moral and cultural factors in determining responsible consumption behavior. Adding more variables to the TPB model has expanded research on industrial and consumer decision-making behavior.